Perancangan Ruang Komunal Mahasiswa Berbasis Arsitektur Perilaku Sunda - Akhmad Farisan Garnida; Noor Cholis Idham (LPPM Universitas Sangga Buana, 2026)
Communal space is a space intended to accommodate diverse activities while still referring to aspects of safety and comfort. Communal spaces in campus areas often do not meet the needs of their users and do not consider behavioral architecture in the design process. West Java province is one of the provinces with the largest number of students in Indonesia, and most of its students are of Sundanese ethnicity. The purpose of this study is to analyze the appropriate needs of communal space based on Sundanese behavioral architecture. The research method used is a quantitative descriptive method with data collection techniques in the form of questionnaires. The results show that Sundanese cultural values, habits, and behaviors can influence an individual’s perception within communal spaces. The quality of communal space is highly determined by the extent to which the space aligns with the behavioral needs of its users.